2015
DOI: 10.5433/1679-0359.2015v36n3supl1p1895
|View full text |Cite
|
Sign up to set email alerts
|

Doses of N, P and K in the cultivation of eucalyptus in soil originally under Cerrado vegetation

Abstract: Many eucalyptus plantations in Brazil are in areas of soil with low fertility, with little phosphorous (P) and potassium (K) availability and with low organic matter (OM) content, resulting in a low supply of nutrients to plants, directly reflected in reduced yield. Thus, our objective was to evaluate the effects of nitrogen (N), P and K fertilization on the growth of eucalyptus plants, with the aim of achieving nutritional balance and high yield. The experiment was conducted on Renascença Farm, an agricultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 11 publications
1
18
1
6
Order By: Relevance
“…A moderate Mg deficiency was observed in Eucalyptus, which explains this reduction in the LCI and plant growth. Gazola et al [29], under the same soil and climatic conditions, found that increasing the K dosage resulted in an increase in the K concentrations in the leaves and a decrease in the Ca and Mg concentrations in the Eucalyptus.…”
Section: Concentrations Of N and P In The Leaves And In The Littermentioning
confidence: 99%
See 1 more Smart Citation
“…A moderate Mg deficiency was observed in Eucalyptus, which explains this reduction in the LCI and plant growth. Gazola et al [29], under the same soil and climatic conditions, found that increasing the K dosage resulted in an increase in the K concentrations in the leaves and a decrease in the Ca and Mg concentrations in the Eucalyptus.…”
Section: Concentrations Of N and P In The Leaves And In The Littermentioning
confidence: 99%
“…Under the same soil and climatic conditions, in the first cycle of Eucalyptus, Gazola et al [29] verified that the maximum yield of Eucalyptus was obtained at 21 months of age with the application of 71 kg ha −1 of N, 100 kg ha −1 of P 2 O 5 , and 125 kg ha −1 of K 2 O. Celestrino [33] observed positive results for plant height, DBH, and VW with a dose of 1 kg ha −1 of B applied to the Eucalyptus.…”
Section: Concentrations Of N and P In The Leaves And In The Littermentioning
confidence: 99%
“…While these inputs are less than for common annual crops in the region, fertilizer application may represent a significant operating cost in plantations (Franco et al 2015, Martins et al 2015, Matsuura et al 2017). Fertilization beyond current application rates does not typically increase production following canopy closure , de Gazola et al 2015, Pulito et al 2015. Fertilizer is generally applied only in the first 2-3 yr of the rotation, and companies have investigated consolidating into a single application per cycle (da .…”
Section: Rotation Length and Nirv Early In Rotation Roughly Predict Smentioning
confidence: 99%
“…Mineralizable N and the efficient internal N cycling are considered to suffice their fast growth [47,48]. Seldom responses of eucalypt growth to N fertilization are found in literature and they are usually limited to the first two years, while canopy is still in formation or under N limiting situations [11,[14][15][16][17][18][19][20]. Here, tree height responded positively to N fertilization during the two-year evaluation, even with relatively high initial soil N content and low soil C:N ratio (Table 1).…”
Section: Tree Growthmentioning
confidence: 99%
“…Forest growth is mainly limited by nitrogen (N) and phosphorus (P) in tropical regions [13]. However, the response of eucalypt plantations to N fertilization has been widely discussed and contradictory in the literature [11,[14][15][16][17][18][19][20][21]. Some authors have shown positive responses to N fertilization [11,15,16], especially on initial growth phases [14], while others have shown no response to N supply, suggesting that the soil organic mineralizable N is the main source and sufficient to support tree demand [21][22][23].…”
Section: Introductionmentioning
confidence: 99%